Antagonistic effect between histamine and norepinephrine on isolated guinea-pig right atrium - Giacomini, V. A.; Reis, C. C.A. [UNESP] (Elsevier, 1986)
1. 1. Norepinephrine (NE) and histamine (His) cause a dose related increase in the rate of the guinea pig isolated right atria. 2. 2. The rate increase induced by both amines has been shown to be mediated by pharmacologically different receptors. 3. 3. His shifted the NE CEC to the right in a non parallel fashion. Cimetidine (10-4 mol/l) abolished this antagonism. 4. 4. Norepinephrine (3 × 10-7 mol/l) shifted to the right the His CEC also in a non parallel fashion. Practolol (10-4 mol/l) abolished this antagonism. 5. 5. Theophylline (10-4 mol/l) reverted both: the antagonistic action of His related to the NE chronotropic effect and the antagonistic action of NE related to the His chronotropic effect. 6. 6. The reversal of the antagonism could be the result of the block of purinergic P1-receptors by theophylline. 7. 7. This block impairs the chronotropic effect of adenilic compounds which can function as a modulater of cardiac rate through a negative feed back mechanism. © 1986.